A new diminutive frog species of Adelophryne (Amphibia: Anura: Eleutherodactylidae) from the Atlantic Forest, southeastern Brazil - Lourenço-De-Moraes, Ricardo; Ferreira, Rodrigo Barbosa; Fouquet, Antoine; Bastos, Rogério Pereira (Zootaxa, 2014)
The genus Adelophryne is composed of diminutive frogs occurring in northern Amazonia and the Atlantic Forest. Herein we describe a new species of Adelophryne found in the leaf litter of primary and secondary forests in the mountainous region of Espírito Santo state, southeastern Brazil. The new species is characterized by its small body size, two phalanges in the finger IV, and a glandular ridge line that runs from the posterior part of eye to the insertion of the forelimb. This species is sensitive to edge effect and conversion of native forest into coffee and Eucalyptus plantations and may be listed as Endangered (EN) under B1ab(iii) criteria of the IUCN Red List.